Digital Technology as a Learning Tool and a Driver of Educational Innovation to Enhance Elementary School Students’ Understanding of Mathematics - Huda, Miftahul; Hakim, Faishol; Suhartiningsih , Suhartiningsih; Sunaryati , Titin (ATTA`DIB, 2025)
In today's digital era, technology has become an integral part of the learning process, including in mathematics education at the elementary school level. Although many studies have been conducted on the use of technology in education, there remains a gap in understanding how digital technology can specifically enhance students' understanding of mathematics. This research aims to explore the role of digital technology as a learning tool and a driver of educational innovation in improving elementary school students' understanding of mathematics. This study employs a quantitative approach involving elementary school students as research subjects. Data were collected through surveys and analysis of students' learning outcomes before and after the implementation of digital technology in mathematics learning. The findings indicate that the use of digital technology, such as interactive learning applications and educational videos, significantly enhances students' understanding of mathematical concepts. Students engaged in technology-based learning showed increased motivation and better learning outcomes compared to traditional teaching methods. The study concludes that digital technology can serve as an effective tool for improving elementary school students' understanding of mathematics. With proper implementation, digital technology not only enhances learning outcomes but also creates a more engaging learning environment. This research contributes significantly to the development of mathematics teaching methods in elementary schools and provides insights for educators and policymakers on the importance of integrating technology into education.